Impact of Iran-Israel War on the International Banking System - Gupta, Dr. Shwetam (INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 2025)
This theoretical research paper examines the multifaceted impact of a hypothetical Iran-Israel war on the international banking system. Drawing upon conflict theory in economics and systemic risk theory in international finance, this study explores how heightened geopolitical tensions and potential conflict could cascade through global financial networks. We analyze key mechanisms of transmission, including disruptions to SWIFT transactions, shifts in cross-border capital flows, the implications of escalating sanctions regimes, and the ripple effects of oil-price-induced inflation on banking stability. The paper identifies potential vulnerabilities within different regional banking systems and assesses the crucial role of regulatory institutions such as the IMF, FATF, and BIS in mitigating systemic shocks. Ultimately, this research provides a conceptual framework for understanding the complex interplay between geopolitical conflict and financial fragility, offering theoretical insights into potential risks and suggesting areas for proactive policy responses to safeguard global financial stability. Keywords: Iran-Israel conflict, international banking, systemic risk, geopolitical risk, financial stability, sanctions, oil prices.